SARS-CoV-2 infection induces beta cell transdifferentiation - Tang, Xuming; Uhl, Skyler; Zhang, Tuo; Xue, Dongxiang; Li, Bo; Vandana, J. Jeya; Acklin, Joshua A.; Bonnycastle, Lori L.; Narisu, Narisu; Erdos, Michael R.; Bram, Yaron; Chandar, Vasuretha; et al. (Cell metabolism, 2021)
Recent clinical data have suggested a correlation between coronavirus disease 2019 (COVID-19) and diabetes. Here, we describe the detection of SARS-CoV-2 viral antigen in pancreatic beta cells in autopsy samples from individuals with COVID-19. Single-cell RNA sequencing and immunostaining from ex vivo infections confirmed that multiple types of pancreatic islet cells were susceptible to SARS-CoV-2, eliciting a cellular stress response and the induction of chemokines. Upon SARS-CoV-2 infection, beta cells showed a lower expression of insulin and a higher expression of alpha and acinar cell markers, including glucagon and trypsin1, respectively, suggesting cellular transdifferentiation. Trajectory analysis indicated that SARS-CoV-2 induced eIF2-pathway-mediated beta cell transdifferentiation, a phenotype that could be reversed with trans-integrated stress response inhibitor (trans-ISRIB). Altogether, this study demonstrates an example of SARS-CoV-2 infection causing cell fate change, which provides further insight into the pathomechanisms of COVID-19. [Display omitted] •SARS-CoV-2 viral antigen is detected in beta cells of autopsies of COVID-19 subjects•SARS-CoV-2 infection causes beta cell transdifferentiation•SARS-CoV-2-induced beta cell transdifferentiation is mediated by eIF2 pathway•Trans-ISRIB reverses SARS-CoV-2 infection-induced beta cell transdifferentiation Here, Tang et al. reported the detection of SARS-CoV-2 viral antigen in autopsy samples from COVID-19 subjects. In addition, SARS-CoV-2 infection induces eIF2-pathway-mediated beta cell transdifferentiation, a phenotype that can be reversed by trans-ISRIB.